Integrating open source codes for solid modeling and automatic mesh generation in FEM applications - Neves, Leandro Alves [UNESP]; Machado, José Márcio [UNESP]; Shiyou, Yang (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The applications of the Finite Element Method (FEM) for three-dimensional domains are already well documented in the framework of Computational Electromagnetics. However, despite the power and reliability of this technique for solving partial differential equations, there are only a few examples of open source codes available and dedicated to the solid modeling and automatic constrained tetrahedralization, which are the most time consuming steps in a typical three-dimensional FEM simulation. Besides, these open source codes are usually developed separately by distinct software teams, and even under conflicting specifications. In this paper, we describe an experiment of open source code integration for solid modeling and automatic mesh generation. The integration strategy and techniques are discussed, and examples and performance results are given, specially for complicated and irregular volumes which are not simply connected. © 2011 IEEE.
Keywords: automatic constrained tetrahedralization; FEM applications; solid modelling; Automatic mesh generation; FEM simulations; Integration strategy; Open-source code; Software teams; Solid-modeling; Tetrahedralization; Three-dimensional domain; Computational electromagnetics; Finite element method; Mesh generation; Open systems; Partial differential equations; Three dimensional; Wireless telecommunication systems; Automatic programming